Studi Fenomenologi Makna Kepuasan Kompensasi Bagi Karyawan Generasi Z - Vincentia Ipsita Widyaztuti; Mirwan Surya Perdhana (Faculty of Economics and Business Diponegoro University, 2026)
This study aims to explore how Generation Z employees construct the meaning of compensation satisfaction by examining the financial and non-financial factors that shape their perceptions and experiences. It seeks to understand the subjective meaning they attach to compensation in the workplace. The research also intends to provide insights that help organisations design compensation systems that align with the needs and expectations of younger employees. The research was conducted using a qualitative-phenomenological approach. The research explores the subjective experiences of nine Generation Z informants who are alumni of Diponegoro University and employed across different sectors. The findings indicate that compensation satisfaction is shaped not only by salary but also by the alignment with personal and generational needs, career development opportunities, and organisational culture. Generation Z views compensation as both recognition of effort and a means of achieving well-being, in which non-financial aspects such as work-life balance, learning opportunities, and appreciation are equally important. These insights show that companies should create fair and appropriate compensation systems so that Generation Z employees feel more motivated, engaged, and willing to stay with the company.